Maximum likelihood estimation of misspecified models : twenty years later - Fomby, Thomas B.; Hill, R. Carter (Amsterdam ; Boston : Elsevier/JAI, 2003)
This volume is the result of an Advances in Econometrics conference held in November of 2002 at Louisiana State University in recognition of Halbert White's pioneering work published in Econometrica in 1980 and 1982 on robust variance-covariance estimation and quasi-maximum likelihood estimation. It contains 11 papers on a range of related topics including the estimation of possibly misspecified error component and fixed effects panel models, estimation and inference in possibly misspecified quantile regression models, quasi-maximum likelihood estimation of linear regression models with bound.
Comparative study of pure and pretest estimators for a possibly misspecified two-way error component model / Badi H. Baltagi, Georges Bresson, Alain Pirotte - Estimation, inference, and specification testing for possibly misspecified quantile regression / Tae-Hwan Kim, Halbert White - Quasimaximum likelihood estimation with bounded symmetric errors / Douglas Miller, James Eales, Paul Preckel - Consistent quasi-maximum likelihood estimation with limited information / Douglas Miller, Sang-Hak Lee - An examination of the sign and volatility switching arch models under alternative distributional assumptions / Mohamed F. Omran, Florin Avram - estimating a linear exponential density when the weighting matrix and mean parameter vector are functionally related / Chor-yiu Sin- Testing in GMM models without truncation / Timothy J. Vogelsang - Bayesian analysis of misspecified models with fixed effects / Tiemen Woutersen - Tests of common deterministic trend slopes applied to quarterly global temperature data / Thomas B. Fomby, Timothy J. Vogelsang - The sandwich estimate of variance / James W. Hardin - Test statistics and critical values in selectivity models / R.Carter Hill, Lee C. Adkins, Keith A. Bender - Introduction / Thomas B Fomby, R.Carter Hill.
Includes bibliographical references.
lje 28/01/14
Loans
Keywords: Econometrics; Econometric models